Материалы к фауне трематод дроздовых (Turdidae) Украины - Искова, Н.И. (Вестник зоологии, 1979)
In various regions of the Ukraine 208 samples of 14 Turdidae species were studied. Infestation extensity was 27.9%. The trematodes were not found only in Monticola saxatilis, Oenanthe hispanica and Phoenicurus phoenicurus. Turdus musicus L., and Turdus merula L. are infested most of all. In all 22 species of trematodes belonging to 12 genera, 8 families were detected. Redescription of species new for the Ukrainian fauna and a brief ecologo-parasitological analysis of the data are given.